Usefulness of a Telemedicine Program in Refractory Older Congestive Heart Failure Patients - Burdese, Emanuela (Diseases, 2018)
Background: Home telemonitoring is a modern and effective disease management model that is able to improve medical care, quality of life, and prognosis of chronically ill patients, and to reduce expenditure. The objective of this study was to evaluate the efficacy, costs, and patients’ and caregivers’ acceptance of our model of telemedicine in a high-risk chronic heart failure (CHF) older population. Methods: Patients with high risk/refractory CHF were included. In the case of alarm parameters’ modifications, a cardiologist decided to inform the emergency department (ED), the patient’s General Practioner, or to programme a clinical ambulatory control. Results: Forty-eight CHF patients (28 males; 58.3%), with a mean age of 80.4 ± 7.7 years, entered this clinical experience. During the 20-months follow-up, four patients dropped out from counselling (8.3%), ambulatory clinical control within-24 h was planned in 18% of patients, 11% of patients were admitted to an ED, and 18% were hospitalized. Thirteen patients (29.5%) died a cardiac death; hospital admissions for heart failure decreased during the year after the enrolment when compared to the year before (from 35 to 12 acute HF hospitalizations/year; p = 0.0001). Moreover, in these HF patients followed, accesses to an ED for an acute episode of HF decompensation reduced from 21/year to five/year (p = 0.0001). The economic expenditure, calculated for the year before and after the enrolment, reduced from 116.856 Euros to 40.065 Euros/year. Conclusions: A telemedicine surveillance in high-risk older CHF patients determines a continuous and active contact between patients/caregivers, the Heart Failure Clinic, and family physicians, permitting an early evaluation of signs and symptoms of acute decompensation.